1992
DOI: 10.1159/000175809
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Cigarette Smoking

Abstract: The risk of cardiovascular morbidity and mortality is greatly affected by cigarette smoking. In order to study the pressor response to smoking, 10 normotensive and 10 mild or moderate essential-hypertensive smokers ( > 20 cigarettes daily) were compared with 2 comparable groups of non-smokers. All subjects were asked to smoke 4 cigarettes during 1 h; blood pressure (BP) and heart rate (HR) were monitored beat-to-beat by a non-invasive device (Finapres Ohmeda) during the smoking period and during the immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
1
13
0
2
Order By: Relevance
“…Experimental studies in men and animals have shown that smoking or nicotine administration produces small acute increases in blood pressure and heart rate, presumably due to release of catecholamines (United States Department of Health and Education and Welfare; Public Health Service 1979). This acute blood pressure increase has been attributed to smoking-induced vasoconstriction and accelerated heart rate (Aronow et al 1971;Cellina et al 1975;Cryer et al 1976;Benowitz et al 1982;Benowitz et al 1984;De Cesaris et al 1991;De Cesaris et al 1992;Groppelli et al 1992). Moreover, Istvan et al (1999) reported that the level of salivary cotinine, a nicotine metabolite, was positively correlated with blood pressure in long-term smokers, suggesting that long-term nicotine exposure might be related to modest elevations in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in men and animals have shown that smoking or nicotine administration produces small acute increases in blood pressure and heart rate, presumably due to release of catecholamines (United States Department of Health and Education and Welfare; Public Health Service 1979). This acute blood pressure increase has been attributed to smoking-induced vasoconstriction and accelerated heart rate (Aronow et al 1971;Cellina et al 1975;Cryer et al 1976;Benowitz et al 1982;Benowitz et al 1984;De Cesaris et al 1991;De Cesaris et al 1992;Groppelli et al 1992). Moreover, Istvan et al (1999) reported that the level of salivary cotinine, a nicotine metabolite, was positively correlated with blood pressure in long-term smokers, suggesting that long-term nicotine exposure might be related to modest elevations in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although some studies have reported that no association exists between smoking habits and blood pressure, 31,32 each cigarette induces a similar and statically significant increase in both blood pressure and heart rate which lasts for a long time. 33 This is further demonstrated by the positive effect of smoking on blood pressure and also by analysing the amount of nicotine in cigarettes statically -proving that there were significant increases in systolic and diastolic blood pressure in smokers. 33,34 While the problem of heterogeneity appeared in the included studies, research makes it difficult to synthesise the findings, although it is possible to identify issues for further research.…”
mentioning
confidence: 88%
“…33 This is further demonstrated by the positive effect of smoking on blood pressure and also by analysing the amount of nicotine in cigarettes statically -proving that there were significant increases in systolic and diastolic blood pressure in smokers. 33,34 While the problem of heterogeneity appeared in the included studies, research makes it difficult to synthesise the findings, although it is possible to identify issues for further research. Control of HTN has become of the utmost importance in Pakistan as the incidence of cardiovascular complications is rising sharply in this region.…”
mentioning
confidence: 88%
“…Many reported that smokers had a similar or lower blood pressure than nonsmokers [15][16][17], and part of the reason given was the lighter body weight of smokers [18]. On the other hand, because of the immediate effect of nicotine in raising blood pressure [19,20], smokers were consistently found to have a higher blood pressure when monitored around the clock [8,21,22]. For those studies reporting that smokers had an elevated blood pressure [13,14,23], some showed dose-response relationships between daily cigarette consumption and blood pressure [13,14].…”
Section: Discussionmentioning
confidence: 99%